Expanding opportunities for the next generation : early childhood development in the Middle East and North Africa - El-Kogali, Safaa; Krafft, Caroline (Directions in development (Washington, D.C.). Human development., 2015)
Early childhood is the most important stage of human development. In the Middle East and North Africa (MENA), there is little research and inadequate investment in this crucial stage of life. This book assesses the state of early childhood development (ECD) in MENA from before birth through age five, examining multiple dimensions of early development including health, nutrition, socio-emotional development, early learning, and early work. The book begins with a discussion of the importance of ECD as a critical foundation for later development, and also as a stage of life when inequality and so.